Pulmonary thromboembolism from familial protein S deficiency - Mohd Tohit, Eusni Rahayu; Seman, Zainina; Idris, Faridah; Leong, Chooi Fun; Cheong, Soon Keng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2007)
Hereditary thrombophilias are a group of inherited conditions that predispose to thrombosis. Most of the inherited thrombotic disorders are associated with venous thromboembolism. Pulmonary embolism represents a major cause of morbidity and mortality. Chronic thromboembolic disease is a'great masquerade' and often mistakenly diagnosed as coronary artery disease, asthma, pneumonia and psychogenic dyspnoea. Recurrent pulmonary embolism with pulmonary hypertension can be missed if awareness of the condition is not created. The consequences of a missed diagnosis can be deadly. We present a case of familial protein S defects leading to recurrent pulmonary thromboembolism.